Lesson plan analysis on Merdeka Mengajar Platform English for Nusantara VII - Sumayyah, Sumayyah (Verba: Journal of Applied Linguistics, 2024)
A Lesson Plan is a written document that serves as the teachers’ guidance during learning (Nessari & Heidari, 2014). Emancipated curriculum simplified some lesson plan formats (Rahayu et al., 2021). This research aimed at (1) analyzing teachers’ lesson plans published in the Merdeka Mengajar Platform following the recent emancipated curriculum format and (2) finding lesson plan components consistent with Brown’s stipulated elements. This research employed a qualitative descriptive approach with document analysis by Bowen (2009) to investigate a lesson plan published in the Merdeka Mengajar Platform. The data were obtained using document analysis, showing that 67% of lesson plans followed the emancipated curriculum.